Surgical Resection After Talimogene Laherparepvec for Melanoma: Persistent Fuorodeoxyglucose Avidity on Positron Emission Tomography Despite No Viable Disease. Issue 6 (June 2021) - MacArthur, Taleen A.; Fahy, Aodhnait S.; Jakub, James W.
Background: Talimogene laherparepvec (TVEC) is an injectable attenuated oncolytic herpes simplex virus (HSV-1) used in the treatment of loco regionally metastatic melanoma. Lesions managed by TVEC are generally considered unresectable at time of initiation of intralesional therapy; however, a subset of patients go on to have surgical resection of loco regionally controlled disease. We sought to review our experience with surgical excision of treated lesions to offer an insight into the radiologic correlate, treatment effect, and pathological findings of intralesional TVEC therapy. Methods: This is a retrospective descriptive case series of patients who underwent TVEC injection at Mayo Clinic, Rochester, MN, between October 2016 and July 2020. Institutional Institutional Review Board approval was obtained. Results: Twenty-one patients underwent intralesional TVEC, met inclusion criteria, and were included in this series. Seven went on to surgical excision of the injected lesions after an initial course of TVEC. Of those 7 patients, 4 had residual melanoma in the specimen on final pathology, while 3 had a complete pathologic response. All 3 patients who had no residual disease on pathology continued to have fluorodeoxyglucose (FDG) avidity on preoperative positron emission tomography scan of the excised lesions. Discussion: Despite ongoing FDG avidity on PET scan, patients who have well-controlled disease and stability over time of the injected lesions may benefit from surgical excision following a course of TVEC. This may render the patient clinically disease free and/or allow them a reprieve from TVEC treatment.